Upper Ordovician conodonts from the Bowan Park succession, central New South Wales, Australia - Zhen, Yong Yi; Webby, Barry D.; Barnes, Christopher R. (1999)
Some 2379 conodont specimens have been recovered from 50 samples through the 560 m thick Bowan Park Group and the basal part of the Malachi's Hill Beds of Late Ordovician age, from the western side of the Molong high, in central New South Wales. These have been assigned to 32 species including three new species, Panderodus nodus nov. sp., Paroistodus? nowlani nov. sp. and Yaoxianognathus ani nov. sp., and a revised multielement apparatus of the species, Yaoxianognathus? tunguskaensis (Moskalenko). Two stratigraphically, are recognised. They are characterised by the first appearances of T. blandus and T. tumidus, respectively, are recognised. They are correlated with similar faunas in the mid-upper part of the Cliefden Caves Limestone Group and the lower Malongulli Formation of the eastern Molong High in central New South Wales. The Bowan Park fauna as a whole is dominated by Panderodus gracilis (Branson and Mehl), Yaoxianognathus ani nov. sp., Belodina confluens Sweet, Protopanderodus liripipus Kennedy, Barnes and Uyeno and Drepanoistodus suberectus (Branson and Mehl) (72% of total fauna), and shows a mixture of North American Midcontinent and North China affinites. However, influx of some species of North Atlantic Realm aspect mainly occurs in the T. tumidus assemblage which, exhibiting a significant increase in diversity, is preserved in a relatively deeper water facies.